2005
DOI: 10.1016/j.jip.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paenibacillus nematophilus on the entomopathogenic nematode Heterorhabditis megidis

Abstract: The insect parasitic nematodes Heterorhabditis spp. are mutualistically associated with entomopathogenic bacteria, Photorhabdus spp. A novel association has been detected between H. megidis isolate EU17 and the endospore-forming bacterium Paenibacillus nematophilus. P. nematophilus sporangia adhere to infective juveniles (IJs) of H. megidis and develop in insect hosts along with the nematodes and their symbiont. We tested the eVects of P. nematophilus on H. megidis. The yield and quality (size, energy reserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 26 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…For example, while low levels of fusaric acid, a toxin produced by the fungus Fusarium oxysporum , increase production of the antifungal enzyme β-1,3-glucanase by P. polymyxa strains WR-2 and SQR-21, higher levels of fusaric acid actually decrease their production and result in reduced P. polymyxa growth [61]. Furthermore, Paenibacillus may compete with other beneficial organisms [62, 63]. …”
Section: Biocontrolmentioning
confidence: 99%
“…For example, while low levels of fusaric acid, a toxin produced by the fungus Fusarium oxysporum , increase production of the antifungal enzyme β-1,3-glucanase by P. polymyxa strains WR-2 and SQR-21, higher levels of fusaric acid actually decrease their production and result in reduced P. polymyxa growth [61]. Furthermore, Paenibacillus may compete with other beneficial organisms [62, 63]. …”
Section: Biocontrolmentioning
confidence: 99%
“…Concomitant infection by EPNs and Paenibacillus spp. had little measurable effects on nematode reproduction or energy reserves but spore-encumbered IJs were less motile and infected fewer insects (El-Borai et al, 2005;Enright and Griffin, 2005) compared to spore-free IJs. The degree to which Paenibacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Tc orthologues have since been found in other Gramnegative bacteria including Serratia entomophila and X. nematophilus (Hurst et al, 2000;Sergeant et al, 2003) and have also been found in the Gram-positive bacterium Paenibacillus (Enright & Griffin, 2005). This implies that the Tc's may be important in insect pathogens.…”
Section: Introductionmentioning
confidence: 99%